Building Electron/Proton Nanohighways for Full Utilization of Water Splitting Catalysts. Issue 16 (28th February 2020) - Yang, Gaoqiang; Yu, Shule; Kang, Zhenye; Li, Yifan; Bender, Guido; Pivovar, Bryan S.; Green, Johney B.; Cullen, David A.; Zhang, Feng‐Yuan
Abstract: Low electron/proton conductivities of electrochemical catalysts, especially earth‐abundant nonprecious metal catalysts, severely limit their ability to satisfy the triple‐phase boundary (TPB) theory, resulting in extremely low catalyst utilization and insufficient efficiency in energy devices. Here, an innovative electrode design strategy is proposed to build electron/proton transport nanohighways to ensure that the whole electrode meets the TPB, therefore significantly promoting enhance oxygen evolution reactions and catalyst utilizations. It is discovered that easily accessible/tunable mesoporous Au nanolayers (AuNLs) not only increase the electrode conductivity by more than 4000 times but also enable the proton transport through straight mesopores within the Debye length. The catalyst layer design with AuNLs and ultralow catalyst loading (≈0.1 mg cm −2 ) augments reaction sites from 1D to 2D, resulting in an 18‐fold improvement in mass activities. Furthermore, using microscale visualization and unique coplanar‐electrode electrolyzers, the relationship between the conductivity and the reaction site is revealed, allowing for the discovery of the conductivity‐determining and Debye‐length‐determining regions for water splitting. These findings and strategies provide a novel electrode design (catalyst layer + functional sublayer + ion exchange membrane) with a sufficient electron/proton transport path for high‐efficiency electrochemical energy conversion devices. Abstract : Easily accessible gold nanolayers with straight mesopores are discovered to build electron/proton highways for novel multiple‐layer (catalyst layer + functional sublayer + proton exchange membrane) water splitting electrodes. A new coplanar‐electrode proton exchange membrane water electrolyzer bridges the gap between catalyst development and real electrolyzer applications. Two reaction‐determining regions are proposed to guide electrode development in practical electrochemical devices.